THE POTENTIAL OF PUBLIC-PRIVATE PARTNERSHIP’S EMPLOYMENT IN URBAN PASSENGER TRANSPORT SPHERE IN OMSK - E. B. Lerman; S. A. Teslova (Вестник СибАДИ)
Authors consider concept of public-private partnership, forms of its implementation. The Legislative acts, regulating the activities public-private partnerships, and features of Russian and foreign application experience are studied. It presents analyses of statistical indicators and situation in urban public transport sphere in Omsk, on which results identified the necessity and investigate the opportunity of public-private partnership principles applying taking into account the specifics of the regional market.